Efficacy and safety of ibuprofen in infants aged between 3 and 6 months - Ziesenitz, Victoria C. (Pediatric drugs, 2017)
Ibuprofen is a non-steroidal anti-inflammatory drug frequently administered to children of various ages for relief of fever and pain and is approved as an over-the-counter medication in many countries worldwide. Although there are extensive data on its efficacy and safety in children and adults, there are divergent dosing recommendations for analgesia and treatment of fever in infants, especially in the age group between 3 and 6 months of age. In this article, we have assessed the safety and efficacy of ibuprofen use in infants in an attempt to find the optimal method of pain and fever management in this specific age group. Based on the current evidence, short-term use of ibuprofen is considered safe in infants older than 3 months of age having a body weight above 5-6 kg when special attention is given to the hydration of the patient. Ibuprofen should be prescribed based on body weight using a dose of 5-10 mg/kg. This dose can be administered 3-4 times a day resulting in a maximum total daily dose of 30-40 mg/kg. The rectal route has been shown to be less reliable because of erratic absorption, especially in young infants. Since most efficacy and safety data have been derived from trials in infants with fever, future studies should focus on the efficacy of ibuprofen in young infants with pain.
Gesehen am 17.08.2018